2022
DOI: 10.3389/fbioe.2022.917765
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Phosphate/Hyaluronic Acid Composite Hydrogels for Local Antiosteoporotic Drug Delivery

Abstract: Despite the bone ability of self-regeneration, large bone defects require surgical intervention. Likewise, when it comes to osteoporotic bone fractures, new approaches should be considered a supportive mechanism for the surgery. In recent years, more and more attention has been attracted to advanced drug delivery systems for local osteoporosis treatment, combining appropriate biomaterials with antiosteoporotic drugs, allowing simultaneously to regenerate the bone and locally treat the osteoporosis. Within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Calcium phosphate nanoparticles can be incorporated into hydrogels to create a composite material that mimics the composition of natural bone. 102 The addition of nanoparticles enhances the mechanical properties of hydrogel and promotes osteogenic differentiation of stem cells. Hu et al reported the development of nanocomposite hydrogel with improved mechanical properties using polyacrylamide/nano-hydroxyapatite (nHAp) for better adhesion of mesenchymal stem cells (MSCs) and osteogenic differentiation promotion.…”
Section: Advantages Of Nps Incorporated Hydrogels In Delivery Of the ...mentioning
confidence: 99%
“…Calcium phosphate nanoparticles can be incorporated into hydrogels to create a composite material that mimics the composition of natural bone. 102 The addition of nanoparticles enhances the mechanical properties of hydrogel and promotes osteogenic differentiation of stem cells. Hu et al reported the development of nanocomposite hydrogel with improved mechanical properties using polyacrylamide/nano-hydroxyapatite (nHAp) for better adhesion of mesenchymal stem cells (MSCs) and osteogenic differentiation promotion.…”
Section: Advantages Of Nps Incorporated Hydrogels In Delivery Of the ...mentioning
confidence: 99%
“…Osteoporosis is a systemic metabolic malady whereby the equilibrium of bone homeostasis, overseen by osteoblasts and osteoclasts in the context of osteoporotic skeletal tissue undergo disruption and accelerated remodeling, ultimately resulting in augmented brittleness of osseous structures and considerably strontium ranelate for drug delivery in the treatment of localized osteoporosis. [11] Li et al used the functionality of a temperaturesensitive hydrogel as a delivery vehicle for vancomycin liposomes aim to impede the rapid release of vancomycin and DNase 1, thus establishing a sterile milieu conducive to fostering fracture healing in osteoporotic bone afflicted with fracture-related infections (FRIs). [12] In contrast to conventional hydrogels, injectable hydrogels are administered in a minimally invasive manner through a syringe needle to precisely target sites.…”
Section: Introductionmentioning
confidence: 99%
“…However, alginate low entrapment e ciency due to facile drug leaching and the burst release of entrapped drug as a result of alginate disintegration in basic media were unavoidable. Acyclovir is model drug based on cellulose hydrogel composition (βcyclodextrin/ carboxymethylcellulose) used for controlled distribution mechanism for drug [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous study, homogenous alginate/CaCO 3 composite micro particles made utilizing micro uidic technology demonstrated pH-sensitive sustained release of trypan blue (model drug) depended on their compositions when studied for wound healing application [11]. Composite hydrogels of calcium phosphate and hyaluronic acid were used for the delivery of local anti-osteoporotic drug strontium ranelate (SrRan) [10]. Moreover, pH sensitive hydrogel based on sodium carboxymethyl cellulose and poly(methacrylic acid) were also studied for oral administration of insulin [12].…”
Section: Introductionmentioning
confidence: 99%